Development and Validation of a Two-Step Predictive Risk Stratification Model for Coronavirus Disease 2019 In-hospital Mortality: A Multicenter Retrospective Cohort Study - Li, Yang; Kong, Yanlei; Ebell, Mark H.; Martinez, Leonardo; Cai, Xinyan; Lennon, Robert P.; Tarn, Derjung M.; Mainous, Arch G.; Zgierska, Aleksandra E.; Barrett, Bruce; Tuan, Wen-Jan; Maloy, Kevin; et al. (Frontiers in Medicine, 2022)
OBJECTIVES: An accurate prognostic score to predict mortality for adults with COVID-19 infection is needed to understand who would benefit most from hospitalizations and more intensive support and care. We aimed to develop and validate a two-step score system for patient triage, and to identify patients at a relatively low level of mortality risk using easy-to-collect individual information. DESIGN: Multicenter retrospective observational cohort study. SETTING: Four health centers from Virginia Commonwealth University, Georgetown University, the University of Florida, and the University of California, Los Angeles. PATIENTS: Coronavirus Disease 2019-confirmed and hospitalized adult patients. MEASUREMENTS AND MAIN RESULTS: We included 1,673 participants from Virginia Commonwealth University (VCU) as the derivation cohort. Risk factors for in-hospital death were identified using a multivariable logistic model with variable selection procedures after repeated missing data imputation. A two-step risk score was developed to identify patients at lower, moderate, and higher mortality risk. The first step selected increasing age, more than one pre-existing comorbidities, heart rate >100 beats/minute, respiratory rate ≥30 breaths/minute, and SpO2 <93% into the predictive model. Besides age and SpO2, the second step used blood urea nitrogen, absolute neutrophil count, C-reactive protein, platelet count, and neutrophil-to-lymphocyte ratio as predictors. C-statistics reflected very good discrimination with internal validation at VCU (0.83, 95% CI 0.79–0.88) and external validation at the other three health systems (range, 0.79 to 0.85). A one-step model was also derived for comparison. Overall, the two-step risk score had better performance than the one-step score. CONCLUSIONS: The two-step scoring system used widely available, point-of-care data for triage of COVID-19 patients and is a potentially time- and cost-saving tool in practice.